Pemanfaatan Akun Instagram @baznasindonesia sebagai Media untuk Mengedukasi Zakat Kepada Masyarakat - Popi Nuranisa; Asriyani Sagiyanto; Fajar Diah Astuti (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to examine the utilization of the official Instagram account @baznasindonesia as a digital platform for educating the public about zakat. In today’s era of rapid technological development, social media, particularly Instagram, has become an effective medium for disseminating information, raising awareness, and enhancing public participation in zakat. The research method employed is qualitative descriptive, with data collected through interviews, observations, and documentation. The findings reveal that BAZNAS leverages various Instagram features such as carousel feeds, reels, and Stories to present educational content that is engaging, easy to understand, and aligned with the communication style of younger generations. Furthermore, interaction with the public is strengthened through the comments section and Direct Messages (DM), enabling responsive two-way communication. Challenges encountered include ensuring information accuracy, addressing negative comments, and adapting content to the fast-changing digital trends. Nevertheless, BAZNAS seeks to innovate by collaborating with influencers, public figures, and partner institutions to expand the reach of zakat education. This study concludes that the @baznasindonesia Instagram account has proven effective in enhancing zakat literacy, building public trust, and reinforcing the institution’s image as the official zakat management authority in Indonesia. The findings are expected to contribute to the development of digital communication strategies in Islamic philanthropy and da’wah, as well as provide a useful reference for future research exploring other social media platforms with different methodological approaches.